Violence Experience among Immigrants and Refugees: A Cross-Sectional Study in Italy - Francesco Napolitano (BioMed Research International, 2018)
The objectives of this cross-sectional investigation among a random sample of immigrants and refugees in Italy were to gain an insight into the extent and type of the episodes of violence and to assess their association with different characteristics. Data was collected from September 2016 to July 2017 using a face-to-face structured interview. A total of 503 subjects participated. Overall, 46.5% and 40% of the sample reported having experienced some form of violence in Italy at least once since they arrived and during the last 12 months. Psychological violence was the most common form experienced by 53.2% of the participants, 40.3% experiencing physical violence, 18.9% economic violence, and only 6.5% intimate partner violence. The risk of experiencing at least one form of violence in the last 12 months in Italy was more likely to occur among immigrants who have been in Italy much longer and less likely in those who lived in a camp. The number of episodes of violence experienced since they arrived in Italy was significantly higher in female, in those who have been in Italy much longer and in those who had experienced at least one racially discriminatory episode of violence, whereas those with middle and high school or above educational level and those who did not experience psychological consequences of the violence had experienced a lower number of episodes. These results must be used to strengthen interventions and policies aimed at preventing violence among this population.